2019
DOI: 10.1097/mjt.0000000000000652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Citalopram for the Treatment of Neurocardiogenic Syncope

Abstract: Citalopram seems to have desirable effects on NCS and patient well-being. Diagnostic use of the HUTT is useful for confirming diagnoses of NCS but is not likely to improve patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…A recent study demonstrated that fluoxetine could be considered as the first-line treatment in VVS patients with recurrent syncope episodes and psychogenic disorders [46]. Similarly, Kadri et al observed a significant improvement with citalopram treatment in syncope patients when the primary endpoint was considered as a well-being score (WS) [47]. Because syncope might occur secondary to psychiatric disorders, these findings showed the importance of evaluation of the psychiatric status.…”
Section: -Tse Was Correlated Significantly and Positively Withmentioning
confidence: 97%
“…A recent study demonstrated that fluoxetine could be considered as the first-line treatment in VVS patients with recurrent syncope episodes and psychogenic disorders [46]. Similarly, Kadri et al observed a significant improvement with citalopram treatment in syncope patients when the primary endpoint was considered as a well-being score (WS) [47]. Because syncope might occur secondary to psychiatric disorders, these findings showed the importance of evaluation of the psychiatric status.…”
Section: -Tse Was Correlated Significantly and Positively Withmentioning
confidence: 97%
“…Іншою групою медикаментозних препаратів, які раніше використовувалися у лікуванні вазовагальних синкопе, є селективні інгібітори зворотного захоплення серотоніну. Хоча жодних рандомізованих подвійних сліпих контрольованих досліджень щодо їх ефективності досі не проводилося, деякі автори все ж акцентують увагу на їх позитивному впливі на розвиток ВС і самопочуття пацієнтів [51,52].…”
Section: педіатріяunclassified
“…The consensus is still lacking on the effectiveness of SSRIs on neurocardiogenic syncope. Although recent evidence pointed out positive results of fluoxetine [ 71 ] and citalopram [ 72 ], more randomized clinical trials are needed to come to more consistent conclusions.…”
Section: Other Off-label Applications Of Ssrismentioning
confidence: 99%